2016
DOI: 10.1117/12.2216489
|View full text |Cite
|
Sign up to set email alerts
|

Challenges towards the simulation of GaN-based LEDs beyond the semiclassical framework

Abstract: We discuss some of the key issues to be addressed along the way to complement, and possibly to replace, the standard semiclassical Boltzmann picture with genuine quantum approaches for the simulation of carrier transport and recombination in GaN-based LEDs, with the goal of gradually removing the fitting parameters presently required by semiempirical «quantum corrections» and to better understand the processes responsible for the efficiency droop. As examples of augmented semiclassical models, we present a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…While considerable uncertainty generally surrounds the quantitative description of optical and electrical properties of III-N QWs (see, e.g., refs. [18][19][20]), such uncertainties do not significantly affect the main conclusions of this paper due to the comparative nature of the simulations and since our results mainly focus on the charge transport in the bulk layers. For the surface recombination at the edges of the DHJ active region we employ the simple surface recombination model based on ref.…”
mentioning
confidence: 99%
“…While considerable uncertainty generally surrounds the quantitative description of optical and electrical properties of III-N QWs (see, e.g., refs. [18][19][20]), such uncertainties do not significantly affect the main conclusions of this paper due to the comparative nature of the simulations and since our results mainly focus on the charge transport in the bulk layers. For the surface recombination at the edges of the DHJ active region we employ the simple surface recombination model based on ref.…”
mentioning
confidence: 99%
“…[5] For example, recent measurements have shown that III-N LEDs exhibit notable hot carrier distributions already close to the peak efficiency, [6][7][8][9] suggesting that hot carriers might have a more profound effect on the device characteristics than previously anticipated.…”
Section: Doi: 101002/aelm201600494mentioning
confidence: 97%
“…Group III nitride (III‐N) based light‐emitting diodes (LEDs) are transforming general lighting and display applications due to their very high efficiencies and favorable spectral properties . However, many of the microscopic details of the materials and of LED operation remain poorly understood, presenting an obvious bottleneck for further LED development and optimization . For example, recent measurements have shown that III‐N LEDs exhibit notable hot carrier distributions already close to the peak efficiency, suggesting that hot carriers might have a more profound effect on the device characteristics than previously anticipated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…State‐of‐the‐art modeling approaches for carrier transport in LEDs are based on drift‐diffusion semiclassical models, which either heuristically patch in quantum effects or simply ignore them. Shortcomings of such rather inconsistent carrier transport models often manifest in the prediction of unrealistic turn‐on voltages.…”
Section: Introductionmentioning
confidence: 99%